Study on deformation characteristics of underground pipeline corridors and uneven settlement factors of foundations in sandy chalky soil layer - Zhang, Yulong; Duan, Lincheng; Li, Yuanxiang; Gao, Meiben (Frontiers in Earth Science, 2024)
Uneven settlement phenomenon is very easy to occur in the sandy pulverized ground stratum, the underground pipe corridor longitudinal and transverse stiffness difference is obvious, so that it is easy to crack and deformation due to uneven settlement in this type of stratum. This paper carries out research on uneven settlement and cracking and deformation of Qihe tube corridor, analyzes the reasons leading to uneven settlement and the factors affecting the deformation and cracking of the tube corridor, and provides guidance for foundation treatment and tube corridor repair and mixing and reinforcement. It was found that the concrete structure of the corridor itself had exposed reinforcement, pockmarks and holes, and that cracks on the structure of the corridor sprouted and expanded from these defects. Defects and damages on the concrete structure of the pipeline corridor are contributing factors to the deformation and cracking of the members, and the uneven settlement of the foundation is the main initiating factor for the cracking and deformation. The analysis of the numerical simulation results of similar underground pipeline corridors is carried out, and it is found that the simulation results are consistent with the deformation characteristics of the Qihe pipeline corridor, which further supports the conclusions of this paper. The main stratigraphic factors contributing to the inhomogeneous settlement were found to be the water-rich and loose bodies in the lower part of the strata, as revealed by the physical means and the experimental verification boreholes.Localized hydraulic effects such as pumping further accelerate the uneven settlement of the foundation.